Penerapan Sistem Presensi Online pada Mahasiswa Berbasis Face Recognition dengan Metode Eigenface - Nisa, Aenun; Ramdani, Dandi; Haryanto, Galih; Maeylani, Winni; Saifudin, Aries; Desyani, Teti (Jurnal Informatika Universitas Pamulang, 2021)
At first attendance was done manually by recording students one by one based on a list of student data. This can be time consuming in the process of registering student attendance lists. From these problems, the author will create an online presence system based on facial image recognition (Face Recognition) using the Eigenface Method which is based on the PCA (Principal Component Analysis) algorithm. By using this online presence, it will make it easier to do attendance because it is already using technology. This method is expected to reduce fraud during absenteeism. This system will be implemented among students to facilitate their absence.